2018
DOI: 10.1038/s41598-018-35877-4
|View full text |Cite
|
Sign up to set email alerts
|

High Abundance of genus Prevotella in the gut of perinatally HIV-infected children is associated with IP-10 levels despite therapy

Abstract: Perinatal HIV infection is characterized by faster HIV disease progression and higher initial rate of HIV replication compared to adults. While antiretroviral therapy (ART) has greatly reduced HIV replication to undetectable levels, there is persistent elevated inflammation associated with HIV disease progression. Alteration of gut microbiota is associated with increased inflammation in chronic adult HIV infection. Here, we aim to study the gut microbiome and its role in inflammation in treated and untreated H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 72 publications
2
54
1
Order By: Relevance
“…CD4+/IL-17+ T lymphocytes were negatively correlated with Coprococcus, a bacteria known to be depleted in MS patients (72) and recognized as a beneficial commensal taxon, but correlated positively with Prevotella, whose role on the host physiology is instead more controversial. Some studies point in fact to its pro-inflammatory role in autoimmune diseases (73)(74)(75), while a very recent work indicates that Prevotella histicola can suppress EAE as efficiently as the disease-modifying drug Copaxone (76). This stresses the need for species-level analysis in future microbiome-based studies.…”
Section: Discussionmentioning
confidence: 99%
“…CD4+/IL-17+ T lymphocytes were negatively correlated with Coprococcus, a bacteria known to be depleted in MS patients (72) and recognized as a beneficial commensal taxon, but correlated positively with Prevotella, whose role on the host physiology is instead more controversial. Some studies point in fact to its pro-inflammatory role in autoimmune diseases (73)(74)(75), while a very recent work indicates that Prevotella histicola can suppress EAE as efficiently as the disease-modifying drug Copaxone (76). This stresses the need for species-level analysis in future microbiome-based studies.…”
Section: Discussionmentioning
confidence: 99%
“…also found that the abundance of Prevotella was significantly higher in perinatal HIV‐1‐infected children than in uninfected controls despite ART. The relative abundance of Prevotella positively correlated with the levels of IP‐10 and sCD14, a marker of monocyte activation and microbial translocation, and was inversely associated with the CD4 + T‐cell count . In addition, Dillon et al.…”
Section: Potential Mechanisms Of Incomplete Immune Reconstitutionmentioning
confidence: 97%
“…The relative abundance of Prevotella is positively correlated with CXCL10/IP-10, a proinflammatory and antiangiogenic chemokine, levels and anti-correlated with CD4 + T cells. 45 Another study demonstrated that P. copri levels were positively associated with colonic CD1c + myeloid dendritic cells. 46 Increased Prevotella has been implicated as a potential initiator to disturbance of GBA signaling.…”
Section: Cannabis and The Gut Microbiome In Hivmentioning
confidence: 99%